Pengenalan Makanan Yang Harus Dihindari Lansia Dengan Hipertensi Kolesterol Dan Asam Urat - Hidayah Afnas, Nur; Septiana Arpen, Ratih (Jurnal Pengabdian Masyarakat, 2023)
According to the World Health Organization (WHO), an elderly person is someone who has reached the age of 60 years and over. The elderly are an age group of humans who have entered the final stages of their life. As people get older, they will experience changes both physically and mentally. So it is not surprising that in old age, more and more diseases attack the elderly. In fact, the elderly suffer from not just one disease but several diseases at once. Madina Elderly Posyandu is one of the Elderly Posyandu located in the Koto Katiak Community Health Center Working Area, Padang Panjang City. From the initial survey, data was obtained that the diseases that often attack the elderly there are hypertension, cholesterol and gout. The aim of this community service is for people, especially the elderly, to pay more attention to healthy lifestyles so that they can avoid hypertension, cholesterol and gout by making appropriate efforts in prevention and treatment as early as possible. The method of this activity is lecture, discussion, question and answer and ends with elderly exercise. The outcome of this activity is an increase in elderly knowledge about what foods elderly people with hypertension, cholesterol and gout should avoid.